What can veterinary professionals do? Measuring the effect of one domestic violence training pilot program on veterinary professionals' capacity to recognize, respond, and refer human victims of domestic violence - Paterson, Rochelle; Boller, Elise; Kim, Youna; Hammond, Kate; Diemer, Kristin (Frontiers in Veterinary Science, 2024)
Introduction: Veterinary professionals have a key role in facilitating multi-agency collaboration to prevent and respond to domestic violence (DV) in situations where animals may be directly or indirectly involved. Yet despite their position as potential touchpoints for victim-survivors with animals, many veterinary professionals do not feel equipped to act on suspicions or disclosures of DV. In response to this identified need, one service operating in Melbourne, Australia, developed the Vet-3R's training program (Recognize-Respond-Refer) which was piloted on 65 veterinary professionals in Melbourne's Eastern Metropolitan Region.Methods: This is an exploratory study aimed at measuring the effect of the Vets 3-R's program on veterinary professionals' confidence and capacity to recognize, respond and refer victims of DV. Participants were invited to complete online surveys before and after the training to evaluate their understanding of DV and their capacity to support suspected victim-survivors with animals who present at their service.The pre-training self-evaluation scores indicated that while most veterinary professionals are aware of the link between animal abuse and DV, they lack the confidence to respond and refer individuals when confronted with suspicions or disclosures of abuse. However, upon completion of the Vets 3-R's program, participants reported marked improvements in their ability to recognize, respond, and refer victim-survivors. The most significant improvement could be seen in participants' self-reported ability to respond appropriately to suspicions of DV.Discussion: While results are indicative only due to the small sample size, this study suggests that veterinary professionals may be an underutilized intervention point for DV victim-survivors with animals. The Vet-3R's training program can be a useful tool for increasing effectiveness of this intervention point to safely assist DV victim-survivors. More research on similar programs with a larger cohort of participants would be beneficial to measure the impact of such programs on a wider scale.1 EDVOS has restructured into a different DV services now called Family Violence Free (FVREE). Vet-3R's training is now being offered as 'Animal-3R's' training.